2009
DOI: 10.1111/j.1467-7687.2009.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the neural mechanisms of selective attention in children from different socioeconomic backgrounds: an event‐related brain potential study

Abstract: Previous research indicates that children from lower socioeconomic backgrounds show deficits in aspects of attention, including a reduced ability to filter irrelevant information and to suppress prepotent responses. However, less is known about the neural mechanisms of group differences in attention, which could reveal the stages of processing at which attention deficits arise. The present study examined this question using an event-related brain potential (ERP) measure of selective auditory attention. Thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
311
4
14

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(353 citation statements)
references
References 55 publications
24
311
4
14
Order By: Relevance
“…Taken together, these results are consistent with previous studies that have demonstrated that Low-SES children have lower performance when it comes to: (1) intellectual abilities (Ramey & Campbell, 1991;Smith, Brooks-Gunn, & Klebanov, 1997); (2) the level of vocabulary achieved (Hart & Risley, 1995;Hoff, 2003;Pan, Rowe, Singer, & Snow, 2005) and language comprehension (Noble, Norman, & Farah, 2005;Noble, McCandliss & Farah, 2007); (3) attentional processes (Mezzacappa, 2004;Stevens, Lauinger, & Neville, 2009);and in (4) diverse tasks that values executive functioning (Farah et al, 2006;Noble et al, 2005;Noble et al, 2007).…”
Section: Cognitive Profiles Associated With Sessupporting
confidence: 81%
“…Taken together, these results are consistent with previous studies that have demonstrated that Low-SES children have lower performance when it comes to: (1) intellectual abilities (Ramey & Campbell, 1991;Smith, Brooks-Gunn, & Klebanov, 1997); (2) the level of vocabulary achieved (Hart & Risley, 1995;Hoff, 2003;Pan, Rowe, Singer, & Snow, 2005) and language comprehension (Noble, Norman, & Farah, 2005;Noble, McCandliss & Farah, 2007); (3) attentional processes (Mezzacappa, 2004;Stevens, Lauinger, & Neville, 2009);and in (4) diverse tasks that values executive functioning (Farah et al, 2006;Noble et al, 2005;Noble et al, 2007).…”
Section: Cognitive Profiles Associated With Sessupporting
confidence: 81%
“…Emerging evidence suggests that SES is a predictor of academic achievement. In fact, a body of research supports the notion that problematic attention is the hallmark of lower-income students and that this deficit is strongly associated to academic achievement (Caspi, Wright, Moffit, & Silva, 1998;Farah & Hackman, 2012;Neville et al, 2013;Sampson, Sharkey, & Raudenbush, 2007;Stevens, Lauinger, & Neville, 2009). Poor or lower-SES environments seem to generate significant stress on individuals compromising selective attention with implications for academic achievement.…”
Section: Introductionmentioning
confidence: 92%
“…The cognitive process of obtaining corrective information, new input, feedback, establishing associations and reorganizing present and prior knowledge is possible due to the brain malleability that lasts throughout the lifespan (Stevens et al, 2009). Studies with rodents showed that after exposure to enriching environments, neuroanatomical changes in the form of increased brain size, brain weight and dendritic branching were reported (Bryck & Fisher, 2012).…”
Section: Interventions and Brain Plasticitymentioning
confidence: 99%
“…Some authors contend that a better understanding of the complexity of the neural mechanism of attention would facilitate prompt interventions and the development of appropriate strategies to tackle children's attention deficits (Stevens et al, 2009). In that sense, developmental neuroscientists performed studies with children from different SES backgrounds using a non-invasive technique called event-related-potentials (ERPs) and some also included salivary cortisol tests to understand the mechanism of attention.…”
Section: Lack Of Selective Attention Interferes With Learningmentioning
confidence: 99%